Profil Industri Rumah Tangga Rakik di Kecamatan Pauh Kota Padang - Wira, Variyetmi; Gustati (Jurusan Akuntansi Politeknik Negeri Padang, 2015)
West Sumatra is famous for various types of cuisine that contain a lot of spices, marinades and have good taste. This can be either culinary or cooking traditional cakes. One of the traditional cakes are brittle or known by Rakik. These efforts form of home industry. This study is a survey of two industry tanggga rakik house in the district of Padang Pauh, which had stood for 20 years, namely Mrs. Fatmawati Rakik Enterprises and Enterprises Rakik Mother Yulidar. Various problems faced by the domestic industry of which this is still traditional activities, lack of good financial management, packaging products and trademarks are less attractive, and yet the drafting of financial statements in accordance with standards (SAK-ETAP).